If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13=5-6x
We move all terms to the left:
13-(5-6x)=0
We add all the numbers together, and all the variables
-(-6x+5)+13=0
We get rid of parentheses
6x-5+13=0
We add all the numbers together, and all the variables
6x+8=0
We move all terms containing x to the left, all other terms to the right
6x=-8
x=-8/6
x=-1+1/3
| -x+11=10 | | 19/x=23/100 | | 3(x+7)-1=3x+20 | | 8/p=28.95 | | 10y-5y-5=53.30 | | 5-(-7)=2x+5 | | 19=(-7t)+75 | | 4x=7-5 | | 6x2−10x+8=3x+6 | | 8p-2p=15 | | a÷3+6=12 | | g/4+14=10 | | s/4+13=12 | | 14-2d=10 | | 2p−1=1 | | -80+20d=180 | | -4=-1-3(2p+3)=-1 | | 9^7n+2=3 | | 2.3^x-3^x=81 | | 10•14^6x-2-10=90 | | 10x14^6x-2-10=90 | | 6x-2+132-x=180 | | (x-3)+(x-2)=30 | | -3(x-1)+8(x-3)=6x=+7-5x | | -3(x-1)+8(x-3)=6x= | | 4x-8=10x-20 | | 75=0.8/x | | 14x=20*13 | | 3(x-5)=7x+-6 | | 12.5+g=15 | | -5+6x=5(x+-3)+x | | 3x+7x+3=-39 |